Positive Orientation And Creative Idea As Components Of Public Service Announcements Effectiveness - Makohin, Iryna; Antonova, Olha (My University, 2020)
The article is dedicated to the consideration of creativeness particularities in public service announcements, to the determination of the effectiveness of such approach on the material of public service video "About blood donation" ("Pro donorstvo krovi") from "1+1 media". The specificity of such kind of information as public service announcements is considered, its defining features are outlined. It has been determined that public service announcements need some positive orientation to increase the attention of various social groups to topical problems, and creative approach to coverage of a negative phenomenon, positive orientation and relevant humour become factors of the public service announcement effectiveness.
Keywords: public service announcements; creativeness; advertising video; positive orientation; соціальна реклама; креатив; рекламний відеоролик; позитивна спрямованість; кафедра маркетингу